Note sopra L’Horlà di Maupassant - Guarnieri, Annalena (Metapsychologica - rivista di psicanalisi freudiana, 2023)
The interpretations by O. Rank and J. Lacan of the tale The Horla by Maupassant are not convincing, they refer to the Horla as the depiction of a double. A careful reading of the three versions of the tale brings to light some elements which these interpretations have overlooked and the consideration of which allows for a critical reconstruction which is very different. In fact, in The Horla we find a literary dramatisation of just those aspects which characterise the being with no face or image described by Freud as reality-ego, which represents the first of two times where the genesis of the ego takes place. It’s significant that the figure of the Horla, so similar to the reality-ego and with no characteristics of the double, comes from the pen of an author who had a profound understanding of regression to the most devastating mental illness, and which offers in this way clinical support to the general theory of subj ectivation.